Pineal cysts may promote pubertal development in girls with central precocious puberty: a single-center study from China - Yuan, Shuxian; Lin, Yifan; Zhao, Yixuan; Du, Mengmeng; Dong, Shijie; Chen, Yongxing; Wei, Haiyan (Frontiers in Endocrinology, 2024)
Introduction：Pineal cysts have long been considered a benign intracranial variation. However, in our clinical practice, it has been observed that some children with central precocious puberty (CPP) who have pineal cysts experience rapid progression in adolescent development. Despite this, there is no consensus regarding whether pineal cysts contribute to CPP as one of its organic factors. This study aimed to analyze the clinical characteristics of pineal cysts in children with CPP and explore the potential effects of pineal cysts on puberty development. Methods: This single-center study retrospectively analyzed clinical manifestations, laboratory features, and imaging findings of girls aged 3–10 years who underwent head/pituitary magnetic resonance imaging (MRI) examinations to detect pineal cysts. Statistical analyses were performed according to cyst size, and the clinical data of girls with CPP but without cysts were compared according to age and body mass index. Results: Among 23,245 girls who underwent head/pituitary MRI, the detection rate of pineal cysts was 3.6%, and most were associated with endocrine diseases. The detection rate of pineal cysts in CPP patients was 6.4%, significantly higher than in the 3.0% in patients without CPP. The estradiol levels, luteinizing hormone (LH) peak, LH peak/follicle-stimulating hormone (FSH) peak, uterine body, and cervical length in girls with CPP and cysts were significantly higher than those without cysts. These levels also increased with cyst size. Among girls who underwent follow-up imaging, 26.3% showed an increasing trend in the cyst size. Conclusion: Pineal cysts are relatively common in children with CPP. They may affect the pubertal development process, with larger cysts correlating to faster pubertal development. Therefore, the authors hypothesize that pineal cysts may trigger CPP in some cases, especially when the cysts are larger than 5 mm in size, as indicated by our data.